Mobile Note Application for Bendesa Adat at Bali - Adijaya, Oka Mahardika (Scientific Journal of Informatics, 2019)
Bendesa Adat is the head of village whose job is to coordinate customary matters in the village he leads, for example, the piodalan ceremony and also the dewasa ayu, especially the dewasa ayu pengabenan of the village. Dewasa ayu is a great day in doing an activity that is believed by the people in Bali. Determination of dewasa ayu and also piodalan has the calculations in accordance with the Balinese Calendar such as calculation of wuku, sasih and also pengalantaka that is in the Balinese Calendar. Not everyone understands how to look for dewasa ayu and piodalan that will occur in the village. Bendesa Adat Notes Based on Android are made to make people know about piodalan and dewasa ayu and holidays in Bali. This application consists of three main informations, there are ceremony day information, dewasa ayu information and also piodalan information that has been tried out to the public and from the results of the trial 32% of the community said they were very satisfied, 54% said they were satisfied and 14% said enough satisfied.